Impact of fat mass and distribution on lipid turnover in human adipose tissue - Kirsty L. Spalding (Nature Portfolio, 2017)
Lipid turnover in tissues can be calculated from ratios of different carbon isotopes. Here the authors use this approach to study lipid turnover in two distinct adipose tissue depots and find that, in obese individuals, visceral fat is more lipolytic than subcutaneous fat.